Sørensen test performance is driven by different physiological and psychological variables in participants with and without recurrent low back pain. (February 2019) - Applegate, Megan E.; France, Christopher R.; Russ, David W.; Leitkam, Samuel T.; Thomas, James S.
Abstract: Time to task failure (TTF) on the Sørensen test predicts low back pain (LBP), but mechanisms driving TTF may vary in those with and without recurrent LBP. To determine the physiological and psychological predictors of TTF, 48 sex, age, and BMI matched participants (24 Healthy, 24 LBP) completed psychological surveys, maximal strength assessments, and the Sørensen test. A two-way ANOVA revealed no significant effects of group ( p = 0.75) or sex ( p = 0.21) on TTF. In the full sample, linear regression analyses revealed that normalized Median Power Frequency (MPF) slope of the Erector Spinae (β = 0.350, p < 0.01), the Biceps Femoris (β = 0.375, p < 0.01), and self-efficacy (β = 0.437, p < 0.01) predicted TTF. In the Healthy group, normalized MPF slope of the Erector Spinae (β = 0.470, p < 0.01), the Biceps Femoris (β = 0.437, p < 0.01), and self-efficacy (β = 0.330, p = 0.02) predicted TTF. In the LBP group, trunk mass (β = −0.369, p = 0.04) and self-efficacy (β = 0.450, p = 0.02) predicted TTF. In sum, self-efficacy consistently predicts performance, while trunk mass appears to negatively influence TTF only for those with recurrent LBP.